1997
DOI: 10.1080/10473289.1997.10464422
|View full text |Cite
|
Sign up to set email alerts
|

Composition of PM2.5 and PM10 Aerosols in the IMPROVE Network

Abstract: IMPLICATIONSAlthough the urban PM 10 concentrations reported in the AIRS database show a decreasing trend, no decrease was observed for either PM 10 or PM 2.5 concentrations at IM-PROVE sites with continuous records from 1988 to 1993. This may indicate that the regional background is remaining constant.Many of the samples collected at Shenandoah during the summer showed a significant fraction, up to one-half, of the sulfur in particles larger than 2.5 µm. Some sulfur episodes in the East would be missed if PM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(121 citation statements)
references
References 4 publications
8
111
1
Order By: Relevance
“…Eldred et al 7 reported similar seasonal patterns in the PM 2.5 /PM 10 ratio measured at the Dolly Sods station (1993)(1994): spring (0.58), summer (0.71), fall (0.64), and winter (0.69). However, Malm et al 6 reported differing seasonal ratios in the 1988-1991 period using combined GSMNP, TN, and Shenandoah, VA, IMPROVE data: spring (0.70), summer (0.60) fall (0.64), and winter (0.68).…”
Section: Data Summarymentioning
confidence: 52%
See 2 more Smart Citations
“…Eldred et al 7 reported similar seasonal patterns in the PM 2.5 /PM 10 ratio measured at the Dolly Sods station (1993)(1994): spring (0.58), summer (0.71), fall (0.64), and winter (0.69). However, Malm et al 6 reported differing seasonal ratios in the 1988-1991 period using combined GSMNP, TN, and Shenandoah, VA, IMPROVE data: spring (0.70), summer (0.60) fall (0.64), and winter (0.68).…”
Section: Data Summarymentioning
confidence: 52%
“…This can be compared to similar proportional contributions of 56% (mass concentration of 10.9 µg/m 3 ) at the GSMNP IMPROVE site for March 1988 to February 1991, 6 and 50% (mass concentration of 12.9 µg/m 3 ) for March 1993 to February 1994. 7 From our Chattanooga observations, we would estimate that an approximate 50% reduction in particulate sulfur mass (from 1985 levels) would be needed to reduce the observed fine mass at this site to the level of the annual PM 2.5 standard metric, assuming, of course, that the contribution of nonsulfate mass constituents remains constant.…”
Section: Seasonal Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated speciated IMPROVE data on seasonal and annual time scales, with particular emphasis on total PM 2.5 , PM 10 , SO 4 , carbonaceous, and Se data. 4,5,[8][9][10] They have presented evidence that SO 4 demonstrates homogeneous behavior in the northeastern United States, where SO 4 levels are regionally similar on seasonal and annual time scales.…”
Section: Discussionmentioning
confidence: 99%
“…A multiple-year time series of speciated aerosol data will be used from the Interagency Monitoring of Protected Visual Environments (IMPROVE) monitor network. [4][5][6][7] The IMPROVE network monitors PM 2.5 concentrations in national parks and wilderness areas, and samples have been collected on Wednesdays and Saturdays since 1988. The IMPROVE data provide an opportunity to evaluate an extended time series of speciated PM 2.5 and to test the homogeneity of individual PM 2.5 species on multiple time scales.…”
Section: Discussionmentioning
confidence: 99%